The occurrence of Taraxitrichia Flint & Harris, 1992 (Trichoptera: Hydroptilidae) in Brazil, with description of the final larval stage - Pes, Ana Maria Oliveira; Hamada, Neusa (Zootaxa, 2003)
The larva of Taraxitrichia is described for the first time. The genus has one species, T. amazonensis Flint & Harris, 1992, described from adults collected in Venezuela. The association between adults and immatures was made using the metamorphotype technique. This is the first record of the genus in Brazil; it is based on examination of specimens collected in streams in Presidente Figueiredo County, Amazonas state. Larvae and pupae were collected only associated with freshwater Porifera.